Coordinated optimization of control parameters for suppressing transient overvoltage in wind power DC transmission systems - Zhao, Jie; Dou, Jinqiu; Li, Ming; Wu, Fangjie; Shen, Xiaolin; Liang, Yilin; Shang, Lei (Frontiers in Energy Research, 2024)
With the increasing proportion of new energy in power systems, the instability issues of novel power systems become more prominent. This paper addresses the transient overvoltage problem in wind power DC transmission systems by proposing a method for transient overvoltage suppression based on doubly-fed wind turbines, high-voltage DC transmission systems, and SVC control parameter optimization. The electromagnetic transient model of the wind power DC transmission system is combined with intelligent optimization algorithms through joint invocation to achieve coordinated optimization of control parameters. Case studies validate the effectiveness of the proposed model and method. The results indicate that the improved genetic algorithm, SEGA, proposed in this paper, effectively suppresses overvoltage at the grid connection point of wind turbines. Furthermore, by simultaneously applying coordinated control strategies based on DFIG and SVC and optimizing parameters of HVDC, DFIG, and SVC, transient overvoltage phenomena can be effectively eliminated. due to their advantages such as high transmission capacity, low cost, minimal losses, and unrestricted transmission distances [4][5]. This makes them instrumental in realizing large-scale wind power export and extensive deployment.